An investigation of the adult education method in Imam Sadiq's (AS) School: a content analysis of hadith of Unwan al-Basri - Akbar Sajedi; Mir Mohsen Erfani Rad (Tabriz University of Medical Sciences, 2021)
Background: Education plays an essential role in all aspects of life. It is particularly important in religious affairs. History shows that religious leaders utilized different methods to teach. In Islam, the Holy Prophet and the infallible Imams, especially Imam Baqir (AS) and Imam Sadiq (As), considered spiritual guidance as part of education and always accentuated and attempted to teach practically through their behavior and speech. Islamic teachings have to a large extent reported religious leaders teaching methods. One of the hadiths that focuses on adult education is Hadith of Unwan al-Basri. In this hadith, Unwan al-Basri, aged 94, reports Imam Sadiq's (As) teaching method. The current study aimed to investigate the adult education method in Imam Sadiq (A.S) School. Methods: The Hadith of Unwan al-Basri was investigated through thematic analysis. The basic concepts were first obtained using the data coding process. The basic concepts were then reduced and categorized into sub-themes and themes. Results: The findings showed that the analysis resulted in seventy basic concepts which were reduced into nineteen sub-themes categorized into four themes: characteristics of the teacher, characteristics of the learner, characteristics of the educational environment, and the educational content. Conclusion: One of the most important elements in Imam Sadiq's (AS) teaching method was his emphasis on teaching both practically and theoretically.